Adaptive Public Leadership: Tantangan Kepemimpinan Menghadapi Masyarakat Ekonomi ASEAN (MEA) - Alma'arif Arif (Institut Pemerintahan Dalam Negeri (IPDN), 2016)
Entering the free market era for ASEAN countries or known as “ASEAN Economic Community (AEC) 2015” which is high competitive and a lot of challenges from the changing environment, the existence of an ideal leader is urgent to promote and realize the vision and mission of Indonesia that has been disclosed in the preamble of the 1945 Constitution and translated based on the needs of national, regional territorial provincial and district/city. The leader's ability to adapt new circumstances and understand how to develop subordinates to be able to better handle complex situations, is a great thing that should be a concern for leaders in changes. Adapting means to understand the meaning of a new state, and have the initiative in the ability to adapt and change with a complete practice in a personality shared values, governance, systems, procedures. Then, find the most effective way yet easy to use, for the development and sustainability of the core activities of the organization. The above facts explain that the leadership values determine the success of development in order to optimize and utilize AEC programs especially in free trade, where the market mechanism determines a process of goods and services which also influence human resources that managed by the certain leadership style, especially in the businesses mechanism that have fairness principle. Using the methods of literature study and interviews, this study aims to analyze how the adaptive leadership in the public sector faces the challenges of the AEC. Given that if it is associated with the challenges of the future, a good leader at least has the ability to be adaptive to the uncertainty of the future, the ability to work cross-country and cross-cultural as well as the ability to create an innovative environment.